Effects of Strength-Modified Grinding on the Surface Microstructure and Mechanical Properties of 30CrMnSiA Bearing Steel - Xiaochu Liu; Xiujie Chen; Zhongwei Liang; Tao Zou; Zhaoyang Liu; Bin Hu (Metals, 2022)
The novel strengthen-modified grinding technique (SMGT) treatment was carried out on 30CrMnSiA bearing steels to investigate the effect of jet pressure (0.2–0.6 MPa) and jet angle (30–90°) on its surface micromorphology, microstructure, and mechanical properties. The results show that, under the compound effects of the impact of steel beads and the abrasive powder micro-cutting, the surface of 30CrMnSiA specimens treated by the SMGT has a microstructure with plenty of micropits inside the pits and overlaps between pits. The pit width, depth, and bulge height positively correlate with jet pressure. The pit depth and bulge height positively correlate with jet angle, while the pit width negatively correlates with jet angle. When a pit morphology is produced, plenty of plastic deformation leads to grain refinement, and the lattice distortion induces retained austenite transformation to martensite. Grain refinement and increased martensite content are the main reasons for the significant increase in hardness on the SMGT-treated specimen surface. With the optimized processing parameters, the grain size of the surface was reduced to 10.14 µm, and the martensite content and hardness of the surface layer rose to 51.35% and 377.6 HV0.2.